Intersections of Gender and Ethnicity in "Brown Girl in the Ring" by Nalo Hopkinson : Haitian Diaspora and Hybridity, and the Controlling Images of Black Women - Lipsanen, Paula (My University, 2022)
The topic of my thesis is the analysis of intersections of gender and ethnicity in Nalo Hopkinson's debut novel, "Brown Girl in the Ring" (1998). I do this by focusing on the two main characters, Gros-Jeanne, and Ti-Jeanne. Gros-Jeanne's section concentrates on Haitian diaspora and hybridity while Ti-Jeanne's section centers the controlling images of Black women. The aim is to answer the following questions: (1) How does gender intersect with ethnicity by emphasising the oppression of Black women? (2) How does Gros-Jeanne and Ti-Jeanne fight the oppression? The framework for my analysis comes from Black Feminism and intersectionality. Barbara Smith, bell hooks, Barbara Christian, and Patricia Hill Collins form the base of the theory, but other critics are also used throughout the thesis. The purpose is to shed light onto the unique experiences of Black women. The analysis revealed that being Black and female are always intra-connected. Having Haitian heritage makes Gros-Jeanne the Other of the society, and her Haitian practices of herbal medicine are simultaneously shunned and exploited. Ti-Jeanne, on the other hand, is forced to live with the images of the matriarch and the sapphire created for Black women to justify their oppression. They both fight the injustice by demonstrating their Black womanhood is what also makes them strong.
Keywords: Brown Girl in the Ring, black feminism, controlling images, diaspora, ethnicity, feminism, gender, hybridity, intersectionality, Nalo Hopkinson, matriarch, Otherness, patriarchy, racism, sapphire, sexism